A Stable Bilayer Polypyrrole‐Sorghum Straw Evaporator for Efficient Solar Steam Generation and Desalination. (13th January 2022) - Li, Yongchao; Xu, Linqiong; Cai, Jiayuan; Liu, Jinhua; Lv, Bizhi; Chao, Jiabao; Zhang, Qiaohong; Zhao, Yongqing
Abstract: Solar desalination is one of the most promising technologies for alleviating the shortage of fresh water. In recent years, interfacial solar evaporators have attracted much attention due to their higher energy efficiency compared to traditional technologies that directly heat bulk water. However, its development has been hampered by the complex preparation process, high costs, and low evaporation performance. Here, a bilayer biomass solar interfacial evaporator—polypyrrole‐sorghum straw (PPy‐SS) evaporator—by coating PPy on the cross section of natural SS is developed via a facile in situ polymerization method at room temperature. The upper PPy layer can achieve a light absorption of about 96% in the range of 200–2500 nm and convert light energy into heat to evaporate water; the lower SS layer can provide continuous water supply to the PPy layer and localize the heat onto the PPy layer. The PPy‐SS evaporator achieves an evaporation rate of 1.385 kg m −2 h −1 and a high evaporation efficiency of 81.9% under 1 Sun illumination. Furthermore, PPy‐SS evaporator displays excellent performance in desalination of seawater. Therefore, such PPy‐SS solar evaporator has great potential for application in solar desalination to alleviate the shortage of freshwater resources. Abstract : A novel biomass‐based bilayer interfacial evaporator, Polypyrrole‐Sorghum Straw (PPy‐SS) is fabricated by coating PPy on the surface of SS. The evaporation rate of PPy‐SS can reach 1.385 kg m −2 h −1, corresponding to a high evaporation efficiency of 81.9%. The desalinated water obtained by the PPy‐SS evaporator meets the drinking water standards of the World Health Organization.